Search for the X (5568) state decaying into Bs0 π± in proton-proton collisions at s =8 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2018)
A search for resonancelike structures in the B0 sπ invariant mass spectrum is performed using protonproton collision data collected by the CMS experiment at the LHC at ffiffi s p ¼ 8 TeV, corresponding to an integrated luminosity of 19.7 fb−1. The B0 s mesons are reconstructed in the decay chain B0 s → J=ψϕ, with J=ψ → μþμ− and ϕ → KþK−. The B0 sπ invariant mass distribution shows no statistically significant peaks for different selection requirements on the reconstructed B0 s and π candidates. Upper limits are set on the relative production rates of the Xð5568Þ and B0 s states times the branching fraction of the decay Xð5568Þ → B0 sπ. In addition, upper limits are obtained as a function of the mass and the natural width of possible exotic states decaying into B0 sπ.